2019
DOI: 10.1186/s13104-019-4323-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of anemia with sensorineural hearing loss: a systematic review and meta-analysis

Abstract: Objective Evidence shows that anemic individuals are at a higher risk of hearing loss. However, there is no systematic review and meta-analysis study. Thus, we aimed to meta-analyze the existing evidence on the association of iron deficiency anemia (IDA) with sensorineural hearing loss (SNHL). We searched PubMed, MEDLINE, Embase, Scopus, and Google Scholar from inception through October 30, 2017, for studies done on the association of the IDA with SNHL. Pooled odds ratio (OR) was calculated by ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…There are also studies linking iron levels and total bilirubin values with SNHL. [16,17] In our study, the RBC, Htc, and Hb values were found to be significant. There was no difference between the patient groups regarding the NLR (generally high in patients with sudden SNHL) and the PDW.…”
Section: Discussionsupporting
confidence: 53%
“…There are also studies linking iron levels and total bilirubin values with SNHL. [16,17] In our study, the RBC, Htc, and Hb values were found to be significant. There was no difference between the patient groups regarding the NLR (generally high in patients with sudden SNHL) and the PDW.…”
Section: Discussionsupporting
confidence: 53%
“…However, the main risk factors of childhood anemia are infection, poor dietary, breastfeeding, and hygiene practices. Poor socioeconomic and education statuses are often the main underlying factors leading to anemia development [15]. Besides, socioeconomic inequality has been shown to be linked to various poor health and nutritional outcomes, including anemia.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of 3-OH-GA in GA-1 patients may lead to increased vulnerability of endothelial structures and subsequent vascular dysfunction. The cochlea is the end organ fed solely by vessels of the labyrinthine artery, making it vulnerable to circulation causes [ 15 ]. Like other toxic metabolic diseases affecting the auditory system, the pathophysiology of hearing loss is still unclear [ 16 ].…”
Section: Discussionmentioning
confidence: 99%